Electrophysiological and Pupillometric Abnormalities in PROM1 Cone–Rod Dystrophy - Park, Jason C. (Transl Vis Sci Technol, 2020)
PURPOSE: To compare electrophysiological and pupillometric responses in subjects with cone–rod dystrophy due to autosomal recessive (AR) PROM1 mutations. METHODS: Four subjects with AR PROM1 dystrophy and 10 visually normal, age-similar controls participated in this study. Full-field, light- and dark-adapted electroretinograms (ERGs) were obtained using conventional techniques. Full-field, light- and dark-adapted measures of the pupillary light reflex (PLR; pupil constriction elicited by a flash of light) were obtained across a range of stimulus luminance using long- and short-wavelength light. Pupil size as a function of stimulus luminance was described using Naka–Rushton functions to derive P(max) (maximum response) and s (pupil response sensitivity). RESULTS: Light-adapted ERGs were non-detectable in all four PROM1 subjects, whereas dark-adapted ERGs were non-detectable in three subjects and markedly attenuated in the fourth. By contrast, each PROM1 subject had light- and dark-adapted PLRs. P(max) ranged from normal to slightly attenuated under all conditions. Light-adapted s was generally normal, with the exception of two subjects who had abnormal s for the long-wavelength stimulus. Dark adapted s was abnormal for each PROM1 subject for the long-wavelength stimulus and ranged from the upper limit of normal to substantially abnormal for the short-wavelength stimulus. CONCLUSIONS: ERG and PLR comparison showed an unanticipated dichotomy: ERGs were generally non-detectable, whereas PLRs were normal for all PROM1 subjects under select conditions. Differences between the measures may be attributed to distinct spatiotemporal summation/gain characteristics. TRANSLATIONAL RELEVANCE: These data highlight the potential usefulness of pupillometry in cases where the ERG is non-detectable.